Directed assembly of liquid metal-elastomer conductors for stretchable and self-healing electronics - Krisnadi, Febby (2021)
Growing interest in soft robotics, stretchable electronics, and electronic skins has created demand for soft, compliant, and stretchable electrodes and interconnects. Here, dielectrophoresis (DEP) is used to assemble, align, and sinter eutectic gallium indium (EGaIn) microdroplets in uncured poly(dimethylsiloxane) (PDMS) to form electrically conducting microwires. There are several noteworthy aspects of this approach. 1) Generally, EGaIn droplets in silicone at loadings approaching 90 wt% remain insulating and form a conductive network only when subjected to sintering. Here, DEP facilitates assembly of EGaIn droplets into conductive microwires at loadings as low as 10 wt%. 2) DEP is done in silicone for the first time, enabling the microwires to be cured in a stretchable matrix. 3) Liquid EGaIn droplets sinter during DEP to form a stretchable metallic microwire that retains its shape after curing the silicone. 4) Use of liquid metal eliminates the issue of compliance mismatch observed in soft polymers with solid fillers. 5) The silicone–EGaIn “ink” can be assembled by DEP within the crevices of severely damaged wires to create stretchable interconnects that heal the damage mechanically and electrically. The DEP process of this unique set of materials is characterized and the interesting attributes enabled by such liquid microwires are demonstrated.